2022
DOI: 10.1136/openhrt-2022-002044
|View full text |Cite|
|
Sign up to set email alerts
|

Individual-level income and out-of-hospital cardiac arrest survival in men and women

Abstract: ObjectiveArea-level socioeconomic factors are known to associate with chances to survive out-of-hospital cardiac arrest (OHCA survival). However, the relationship between individual-level socioeconomic factors and OHCA survival in men and women is less established. This study investigated the association between individual-level income and OHCA survival in men and women, as well as its contribution to outcome variability and mediation by resuscitation characteristics.MethodsA cross-sectional cohort study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The initial rhythm on the electrocardiogram was found to be an important mediator of the SEP-OHCA survival association. Previous studies have suggested that favorable resuscitation characteristics, including witnessed arrest and shorter response time, are associated with initial shockable rhythm . Differences in the etiology of cardiogenic cardiac arrest and disparities in the no-flow time to recognition of OHCA may have also contributed to the association between SEP and initial rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial rhythm on the electrocardiogram was found to be an important mediator of the SEP-OHCA survival association. Previous studies have suggested that favorable resuscitation characteristics, including witnessed arrest and shorter response time, are associated with initial shockable rhythm . Differences in the etiology of cardiogenic cardiac arrest and disparities in the no-flow time to recognition of OHCA may have also contributed to the association between SEP and initial rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic Position and Survival After Out-of-Hospital Cardiac Arrest in Korea characteristics, including witnessed arrest and shorter response time, are associated with initial shockable rhythm. 20,32 Differences in the etiology of cardiogenic cardiac arrest and disparities in the no-flow time to recognition of OHCA may have also contributed to the association between SEP and initial rhythm. Although the initial rhythm is not directly modifiable, interventions to reduce disparities in witnessed status, bystander CPR provision, and no-flow time may be effective.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 99%
“…There is limited literature available on bystander CPR among Nigerian athletes [31,32]. Meanwhile, it has been documented that developing economies could be burdened by sudden cardiac death (SCD) as much as in the developed parts of the globe [33][34][35][36][37]. In fact, the study by Chen et al [33], which is the largest study showing an association between socioeconomic status and survival, and the first study showing an association with bystander CPR, suggested targeting CPR training among the lower socioeconomic groups.…”
Section: Introductionmentioning
confidence: 99%